2008
DOI: 10.1186/1471-2105-9-104
|View full text |Cite
|
Sign up to set email alerts
|

PDTD: a web-accessible protein database for drug target identification

Abstract: BackgroundTarget identification is important for modern drug discovery. With the advances in the development of molecular docking, potential binding proteins may be discovered by docking a small molecule to a repository of proteins with three-dimensional (3D) structures. To complete this task, a reverse docking program and a drug target database with 3D structures are necessary. To this end, we have developed a web server tool, TarFisDock (Target Fishing Docking) , which has been used widely by others. Recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
198
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(201 citation statements)
references
References 26 publications
0
198
0
3
Order By: Relevance
“…This enabled us to predict the function of the proteins and genome annotation that resulted in the identification of potential targets. Screening of the potential drug targets was carried out by similarity search using protein sequence of all the potential targets against the Drug Bank ( Knox et al, 2011), TTD (Chen et al, 2002), PDTD (Gao et al, 2008) and HIT (Ye et al, 2011) to reach the novel drug targets. Further the outer membrane proteins were predicted using Trans-Membrane prediction using Hidden Markov Models (TMHMM), that identify surface membrane proteins which could be used as potential drug targets and vaccine candidates (Krogh et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…This enabled us to predict the function of the proteins and genome annotation that resulted in the identification of potential targets. Screening of the potential drug targets was carried out by similarity search using protein sequence of all the potential targets against the Drug Bank ( Knox et al, 2011), TTD (Chen et al, 2002), PDTD (Gao et al, 2008) and HIT (Ye et al, 2011) to reach the novel drug targets. Further the outer membrane proteins were predicted using Trans-Membrane prediction using Hidden Markov Models (TMHMM), that identify surface membrane proteins which could be used as potential drug targets and vaccine candidates (Krogh et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the library of NMSM derivatives was screened based on their absorption, distribution, metabolism, excretion, and toxicity (ADMET) and Lipinski's rule of five, which resulted in 12 compounds as the best hits. All the 12 compounds were subjected into TarFisDock [41,42] server to find out their protein target. A result of such analysis for the given compounds suggested that they might have an ability to interact with hAChE.…”
Section: Introductionmentioning
confidence: 99%
“…Open-source databases such as DrugBank, the Potential Drug Target Database, Therapeutic Target Database and SuperTarget provide target and drug profiles [2][3][4][5]. These databases feature drug targets, including protein and active site structures, association with related diseases, biological functions and associated signaling pathways [3].…”
Section: Pre-competitive Open-source Drug Discoverymentioning
confidence: 99%